2015
DOI: 10.3923/ajpsaj.2016.52.63
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artificial and Natural Day Light Intensities on some Behavioral Activities, Plumage Conditions, Productive and Physiological Changes for Japanese Quail

Abstract: This study was designed to evaluate the effects of different artificial light intensity; 10, 50, 250, 500 lux and natural day light (NDL, average 375 lux) from 3-18 week of age on behavioral activities, plumage conditions, productive and physiological traits for grower and layer of Japanese quail. A total of 270 Japanese quails chicks (3 week old) were randomly assigned to five treatment groups according to different light intensities. The results showed that the birds subjected at NDL and 250 lux spent signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
1
1
1
Order By: Relevance
“…Other research indicates that artificial light has beneficial economic effects on quail results. The current study revealed that reaction to different light intensities did not influence the level of triiodothyronine hormone level relative to the control group, this result disagrees with pervious study (37) who found that light induces increased releasing of metabolic hormones, including triiodothyronine, thyroxine, insulin, growth hormone and insulin like growth factor-1.…”
Section: Discussioncontrasting
confidence: 99%
“…Other research indicates that artificial light has beneficial economic effects on quail results. The current study revealed that reaction to different light intensities did not influence the level of triiodothyronine hormone level relative to the control group, this result disagrees with pervious study (37) who found that light induces increased releasing of metabolic hormones, including triiodothyronine, thyroxine, insulin, growth hormone and insulin like growth factor-1.…”
Section: Discussioncontrasting
confidence: 99%
“…The mean values of broiler behaviors were affected by different light intensities. These findings are in agreement with the results of Khalil et al (2016) who observed thatdim light reduced eating and drinking behaviour. But, it is contrary to the findings of Newberry et al (1988) who claimed that the light intensity had no effect on the behaviour of eating and drinking.…”
Section: Discussionsupporting
confidence: 93%
“…Untuk memaksimalkan produktivitas, parameter reproduksi dan meningkatkan pendapatan ekonomi dapat menggunakan intensitas cahaya buatan berukuran sedang dengan sistem kandang sisi terbuka untuk produksi puyuh Jepang (Khalil et al, 2016).…”
Section: Hasil Dan Pembahasanunclassified